Digital Financial Risk Control: Challenges and Innovation In The Modern Financial System - Supiati Supiati (PT. Anagata Sembagi Education, 2025)
The rapid expansion of Indonesia’s digital financial ecosystem has significantly advanced financial inclusion and innovation through the growth of fintech platforms, digital payments, and crypto-asset adoption. However, this transformation introduces multifaceted risks, including cyber threats, data breaches, digital fraud, regulatory uncertainty, and money-laundering vulnerabilities associated with crypto-assets and decentralized finance. This study employs a systematic literature review to examine the challenges and innovations in digital financial risk control within Indonesia’s fintech and digital asset sectors. Findings indicate that effective risk mitigation relies heavily on regulatory coordination, advanced supervisory technology, consumer digital literacy, and robust data protection practices. RegTech and SupTech innovations powered by artificial intelligence support real-time risk monitoring and enhance compliance with global standards such as FATF recommendations. Nevertheless, successful digital financial governance also requires algorithmic accountability and ethical technology deployment. This study underscores that safeguarding stability, trust, and consumer protection is essential to achieving a secure and inclusive digital financial system while enabling responsible innovation.